Asymmetric braking and dawnward deflection of dipolarization fronts: Effects of ion reflection. Issue 20 (20th October 2014) - Zhou, Xu‐Zhi; Angelopoulos, Vassilis; Liu, Jiang; Runov, Andrei; Pan, Dong‐Xiao
Abstract Dipolarization fronts (DFs), earthward propagating structures in the Earth's magnetotail with sharp enhancements of the northward magnetic field, can reflect and accelerate ions in the ambient plasma sheet. The ion reflection and acceleration process, which generates earthward flows ahead of the DF, also imposes a dynamic pressure on the DF to decelerate its earthward motion. It has been shown that the ion reflection process is not symmetric, with stronger ion accelerations at the evening side of the DF than at its morning side, which implies dawn‐dusk asymmetric reaction of the ambient plasma and consequently dawnward deflection of DFs. In this paper, we examine this scenario in detail, by carrying out statistical studies based on Time History of Events and Macroscale Interactions during Substorms observations from 2008 to 2011. We demonstrate the important role of the ion reflection process in the longstanding problems regarding DF evolution and bursty flow braking in the near‐Earth plasma sheet.